2018
DOI: 10.3389/fphys.2018.00408
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Performance Investigated With a Novel Smart Compression Garment Based on Pressure Sensor Force Myography and Its Validation Against EMG

Abstract: Muscle activity and fatigue performance parameters were obtained and compared between both a smart compression garment and the gold-standard, a surface electromyography (EMG) system during high-speed cycling in seven participants. The smart compression garment, based on force myography (FMG), comprised of integrated pressure sensors that were sandwiched between skin and garment, located on five thigh muscles. The muscle activity was assessed by means of crank cycle diagrams (polar plots) that displayed the mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…This approach spans the research and development process from sensor design, to measuring the pressure inside a scoliosis brace ( Figure 1 a,b). The sensor was developed from experience in similar sensors of previous projects [ 11 , 12 , 13 , 14 , 25 , 26 , 27 ]. Due to the foam padding inside the scoliosis brace and the knowledge [ 25 ] of how materials placed next to a piezoresistive sensor affect their electrical properties, the two foams involved had to be tested and characterized mechanically.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach spans the research and development process from sensor design, to measuring the pressure inside a scoliosis brace ( Figure 1 a,b). The sensor was developed from experience in similar sensors of previous projects [ 11 , 12 , 13 , 14 , 25 , 26 , 27 ]. Due to the foam padding inside the scoliosis brace and the knowledge [ 25 ] of how materials placed next to a piezoresistive sensor affect their electrical properties, the two foams involved had to be tested and characterized mechanically.…”
Section: Methodsmentioning
confidence: 99%
“…Piezoresistive sensors are relatively cheap but nonetheless sufficiently accurate for measurement of pressure between skin and garments or shoes. For example, Belbasis and Fuss [ 11 , 12 ] and Belbasis et al [ 13 , 14 ] used customized piezoresistive polymers to measure the pressure between the skin and a compression garment for assessment of muscle activity and fatigue (mechanomyography, force-myography (FMG)). Other FMG applications with piezoresistive sensors, encompassing off-the-shelf force sensing resistive (FSR) sensors such as single, multiple, and matrix sensors, have been reported for different applications [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…► What functions do smart garments offer for professional athletes? [34][35][36] ► Microclimate temperature and humidity monitoring 37 38 Other smart functions ► Smart cooling 34 38 39 ► Smart compression 40 on December 1, 2020 by guest. Protected by copyright.…”
Section: Stage 1: Identifying the Research Questionmentioning
confidence: 99%
“…In [ 18 ], the author demonstrated the feasibility of a piezoresistive array armband for hand gesture recognition with three FSR-based sensors. Since both the EMG and FMG can be used for prosthesis control, there are also many studies on the comparison of the EMG and FMG; in some research, it has been shown that the FMG is more stable than EMG over time [ 19 ], while in other research, the EMG is more accurate for muscle fatigue modeling [ 20 ].…”
Section: Introductionmentioning
confidence: 99%